Subplate cells: amplifiers of neuronal activity in the developing cerebral cortex - Heiko J Luhmann; Werner Kilb; Ileana Hanganu-Opatz (Frontiers in Neuroanatomy, 2009)
Due to their unique structural and functional properties, subplate cells are ideally suited to function as important amplifying units within the developing neocortical circuit. Subplate neurons have extensive dendritic and axonal ramifications and relatively mature functional properties, i.e. their action potential firing can exceed frequencies of 40 Hz. At earliest stages of corticogenesis subplate cells receive functional synaptic inputs from the thalamus and from other cortical and non-cortical sources. Glutamatergic and depolarizing GABAergic inputs arise from cortical neurons and neuromodulatory inputs arise from the basal forebrain and other sources. Activation of postsynaptic metabotropic receptors, i.e. muscarinic receptors, elicits in subplate neurons oscillatory burst discharges which are transmitted via electrical and chemical synapses to neighbouring subplate cells and to immature neurons in the cortical plate. The tonic nonsynaptic release of GABA from GABAergic subplate cells facilitates the generation of burst discharges. These cellular bursts are amplified by prominent gap junction coupling in the subplate and cortical plate, thereby eliciting 10 to 20 Hz oscillations in a local columnar network. Thus, we propose that neuronal networks are organized at earliest stages in a gap junction coupled columnar syncytium. We postulate that the subplate does not only serve as a transient relay station for afferent inputs, but rather as an active element amplifying the afferent and intracortical activity.